1996
DOI: 10.1103/physrevlett.77.4620
|View full text |Cite
|
Sign up to set email alerts
|

Optical Study on Phonon Anomalies and Spin Gap inYBa2(Cu1x

Abstract: Optical reflectivity measurements with E k c on YBa 2 ͑Cu 12x Zn x ͒ 3 O 6.6 reveal a dramatic Znsubstitution effect on the anomaly of the in-plane oxygen bending mode and the broad absorption band around 450 cm 21 which are observed at low temperatures for x 0, whereas the low-v suppression of the optical conductivity remains unchanged. This indicates a close relation between the phonon anomaly and the absorption band, while the conductivity suppression is an independent phenomenon. The former suggests a coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 24 publications
4
21
1
Order By: Relevance
“…This behavior involving an anomaly of the Cu-O bending mode, accompanied by the formation of an additional broad absorption band at phonon frequencies, is well studied in the c-axis IR-conductivity of underdoped layered cuprates. 10,11,18,19 The mechanism of this phenomenon is a subject of ongoing discussions. [8][9][10]19 The most favored explanation is based on a model where the bilayer cuprate compounds are treated as a superlattice of inter-and intrabilayer Josephson junctions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior involving an anomaly of the Cu-O bending mode, accompanied by the formation of an additional broad absorption band at phonon frequencies, is well studied in the c-axis IR-conductivity of underdoped layered cuprates. 10,11,18,19 The mechanism of this phenomenon is a subject of ongoing discussions. [8][9][10]19 The most favored explanation is based on a model where the bilayer cuprate compounds are treated as a superlattice of inter-and intrabilayer Josephson junctions.…”
Section: Resultsmentioning
confidence: 99%
“…10,11,18,19 The mechanism of this phenomenon is a subject of ongoing discussions. [8][9][10]19 The most favored explanation is based on a model where the bilayer cuprate compounds are treated as a superlattice of inter-and intrabilayer Josephson junctions. 8,10,11 In this model the additional absorption peak is related to the transverse bilayer plasmon, while the anomalous softening and the loss of the spectral weight of the Cu-O bending mode are explained to be due to the drastic changes of the local electrical fields acting on the in-plane oxygen ions as the Josephson current sets in.…”
Section: Resultsmentioning
confidence: 99%
“…Observations of a broad peak at ∼ 400cm −1 in the optical conductivity which appears below the pseudo-gap temperature have been made by several groups [8,9,10,11,12]. This "400cm −1 " peak has been interpreted as the out-of-phase coupling of the two types of Josephson junctions in YBCO, which correspond to the intra-and the inter-bilayer coupling [17,18].…”
mentioning
confidence: 99%
“…Depending on the anisotropy parameter γ = λ c /λ ab , the Josephson plasma frequency ranges from the microwave (γ ∼ 300 − 1000 for Bi 2 Sr 2 CaCu 2 O 8+δ (Bi-2212) [5,6,7]) to the far infrared frequency (γ ∼ 50 for underdoped YBCO [8,9,10,11,12] and La 2−x Sr x CuO 4 (LSCO) [1,13]). The optical/microwave response originates from the restoration of coherent transport due to the tunneling of superconducting carriers between the CuO 2 layers.…”
mentioning
confidence: 99%
“…For the pseudogap state, the lost spectral weight with suppression is transferred to the higher energy region, while in the superconducting condensation case, it is redistributed as a delta function at ω = 0. It has been shown that the superconducting condensation can be suppressed with Zn-doping [2] that makes easy to observe the features due to the pseudogap.…”
Section: Introductionmentioning
confidence: 99%